Evaluation of holistic sexuality education: A European expert group consensus agreement. (2nd January 2016) - Ketting, Evert; Friele, Minou; Michielsen, Kristien
Abstract : Objectives Holistic sexuality education (HSE) is a new concept in sexuality education (SE). Since it differs from other types of SE in a number of important respects, strategies developed for the evaluation of the latter are not necessarily applicable to HSE. In this paper the authors provide a basis for discussion on how to evaluate HSE. Methods First, the international literature on evaluation of SE in general was reviewed in terms of its applicability to HSE. Second, the European Expert Group on Sexuality Education extensively discussed the requirements of its evaluation and suggested appropriate indicators and methods for evaluating HSE. Results The European experience in SE is scarcely represented in the general evaluation literature. The majority of the literature focuses on impact and neglects programme and implementation evaluations. Furthermore, the current literature demonstrates that evaluation criteria predominantly focus on the public health impact, while there is not yet a consensus on sexual well-being criteria and aspects of positive sexuality, which are crucial parts of HSE. Finally, experimental designs are still considered the gold standard, yet several of the conditions for their use are not fulfilled in HSE. Realising that a new evaluation framework for HSE is needed, the European expert group initiated its development and agreed upon a number of indicators that provide a starting point for further discussion. Conclusions Aside from the health impact, the quality of SE programmes and their implementation also deserve attention and should be evaluated. To be applicable to HSE, the evaluation criteria need to cover more than the typical public health aspects. Since they do not register long-term and multi-component characteristics, evaluation methods such as randomised controlled trials are not sufficiently suitable for HSE. The evaluation design should rely on a number of different information sources from mixed methods that are complemented and triangulated to build a plausible case for the effectiveness of SE in general and HSE in particular. Abstract : 摘要目的 整体型性教育（HSE）是性教育中一种新的理念，由于整体型性教育在很多重要方面和其他类型性教育不同，所以为后者的评价而发展的策略不一定适用于HSE。在这篇文章中作者为如何评价HSE的讨论提供了依据。 方法 首先，复习关于性教育评价的国内外文献，评估其对于HSE的适用性。第二，欧洲性教育专家组广泛讨论整体型性教育评价的要求并且提出评价HSE的适宜的指标和方法。 结果 欧洲在性教育方面的经验几乎可以说是总的关于评价文献的代表。大多数文献关注性教育活动的影响而忽略了对于计划和执行情况的评价。另外，目前的文献资料表明，性教育评价标准主要集中在对公众健康的影响，而关于性满意的标准和性生活积极的方面目前尚没有共识，而这正是HSE至关重要的部分。最后，实验研究设计仍然被看作评价性教育的金标准，但是实验研究设计的一些条件在HSE中不能满足。 意识到需要一个新的针对HSE的评价体系，欧洲专家组开始着手评价体系的发展并且通过一系列的指标，这为进一步的讨论提供了一个起点。 结论 除了对健康的影响以外，性教育方案的质量和方案的实施也值得关注并且应该加以评价。为了适用于HSE，评价标准需要涵盖比传统的公共健康更多的范畴。由于像随机对照实验这样的研究方法不注重长期性和多因素等特征，所以并不是很适合HSE。评价的设计应该依靠很多来自各种方法的不同的信息资源，这些方法互相补充，呈三角形，一起构建一个合理的关于性教育尤其是HSE有效性评价的实例。